Planning for Managed Aquifer Recharge Projects. Issue 5 (23rd July 2022) - McCurry, Gordon; Pyne, David
Abstract: Managed aquifer recharge (MAR) involves the intentional recharge of water to aquifers for subsequent recovery or for environmental benefits. It is an increasingly common water resources management strategy but, despite its use for many decades, is unfamiliar to many. This lack of widespread understanding makes it essential that MAR projects are developed using a systematic, comprehensive and transparent approach. This paper outlines a proven and successful approach to planning and developing MAR projects. The process includes three steps, consisting of developing project objectives, developing evaluation criteria for potential MAR projects, and, after collecting and evaluating pertinent data, ranking potential projects against those criteria. Project objectives help define the data that should be collected and the evaluation criteria that are relevant to consider. Commonly used criteria include those relating to water supply, aquifer restoration, water quality and environmental protection. Key evaluation criteria that are discussed in more detail include the availability of water that would be used for recharge, the suitability of receiving aquifers to accept and retain the recharged water, and the compatibility of recharged water with the aquifer into which it is placed. Potential MAR projects can be ranked objectively by quantifying the evaluation criteria and assigning ranking scores to them. The potential project that best meets the project objectives will score the most favorably. Using a quantitative and objective process to evaluate and rank potential projects will increase support by project stakeholders and increase the likelihood that the project will be successful. Abstract : Article impact statement : Factors to consider when planning a MAR project are presented. These will help in deciding the type, location, design, and feasibility of the project.